Organisation and informational content of the Theileria parva genome - Nene, Vishvanath M.; Morzaria, S.P.; Bishop, Richard P. (Elsevier, 1998)
When compared with other Apicomplexan organisms. Theileria parva has an execptionally small, 10-12 Mbp. genome. There are only 4 chromosomes, each in the Mbp range, and a complete physical map, based on SfiI linking data, is available for each one. A number of genes and cDNAs have been mapped to specific SfiI fragments. Telomeres consist of the simple repeat sequence typical of chromosomal ends but sub-telomeric homologies do not extend beyond 5 kbp. The only dispersed repetitive sequences identified to data are minisatellites, but these are found on a subset of SfiI fragments. There are clusters of distinct multicopy sequences which contain ORFs. However, the majority of parasite protein coding genes are present in a single copy. They have a compact structure, exhibit a bias in codon usage and non-translated regions are small. Introns, if present, are unusually short. Overall, the genome contains remarkably little repetitive, non-coding DNA. The parasite mitochondrial DNA is linear in structure, has a limited protein coding capacity and fragmented rRNA genes and its telomeres contain inverted repeat sequences.